2021
DOI: 10.1101/2021.09.21.21263845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammation and autoreactivity define a discrete subset of patients with post-acute sequelae of COVID-19, or long-COVID

Abstract: Recent studies have demonstrated the significant breadth of emerging autoreactivity in severe SARS-CoV-2 infection. Importantly, we have identified a relaxation of peripheral tolerance within early antibody secreting cells that emerge in patients with COVID-19 as important drivers of those responses. While often viral-specific, these extrafollicular-derived cells also display cross reactivity to autoantigens present in the inflammatory lung environment, and despite resolution of most autoreactivity within 6 mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Presence of autoantibodies was not associated with specific clinical characteristics, results from pulmonary function test or histopathological findings. Thus, they might reflect extrafollicular B cell activation upon contact with SARS-CoV-2 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of autoantibodies was not associated with specific clinical characteristics, results from pulmonary function test or histopathological findings. Thus, they might reflect extrafollicular B cell activation upon contact with SARS-CoV-2 [24].…”
Section: Discussionmentioning
confidence: 99%
“…atMBCs are also associated with the production of autoantibodies in several autoimmune diseases, and were observed to be expanded in the peripheral blood of individuals with PASC prior to the onset of symptoms [13] . Cheon and colleagues [44•] also observed elevated frequencies of activated resident memory-like CD27 + CD69 + B cells in the BAL fluid of aged convalescent subjects, and several studies have shown or suggested a potential relationship between peripheral autoantibody levels and PASC 46 , 47• . Further investigation will be required to determine whether atMBCs and circulating autoantibodies detected in PASC patients contribute to symptoms, or are a consequence of PASC itself.…”
Section: Antigen Persistence In the Absence Of Viral Persistencementioning
confidence: 97%
“…The few studies that have specifically examined autoantibodies in patients with PASC are suggestive that postinfectious autoimmune processes persist. In one cohort of 95 patients with PASC, 80% of the patients had autoantibodies 110 days after infection with SARS-CoV-2 and 40% of the patients had antibodies to two or more immune specificities [46 ▪ ]. Another study of 31 patients, composed primarily of patients with neurological symptoms, found antibodies to β2 adrenoceptor, muscarinic M2 receptor, angiotensin II AT1 receptor, and angiotensin 1–7 MAS receptor [47 ▪ ].…”
Section: Potential Pathogenic Mechanisms Of Postacute Sequelae Of Sev...mentioning
confidence: 99%